Faktor-faktor yang Mempengaruhi Keterlambatan Penyerapan Anggaran Satuan Kerja Kementerian/Lembaga di Wilayah Pembayaran KPPN Jambi - Weni Febriani; Netty Herawaty; Gandy Wahyu Maulana Zulma (LPPM UBP, 2023)
The purpose of this study was to analyze and determine the effect of budget planning, human resources, and procurement of goods/services on delays in budget absorption for work units Ministries/Institutions in the Jambi KPPN environment. This type of research is quantitative with a population of 244 SATKERS at KPPN Jambi. To take a sample of 89 samples used the purposive sampling technique. The research variables are three independent variables, namely budget planning, human resources, and procurement of goods/services, and one dependent variable is the delay in budget absorption. Using multiple linear regression analysis with SPSS 25, the hypothesis was tested to analyze the correlation of the variables. Based on the research results, budget planning affects the delay in budget absorption, human resources affect the delay in budget absorption, and the procurement of goods/services affects the delay in budget absorption.